Understanding Vietnamese college students' self-efficacy beliefs in learning English as a foreign language. (August 2019) - Ngoc Truong, Thi Nhu; Wang, Chuang
Abstract: This article reports on a quantitative study investigating Vietnamese college students' self-efficacy beliefs as related to their English language proficiency and prior learning experience. A sample of 767 Vietnamese first-year college students responded to the Questionnaire of Self-Efficacy Beliefs. Results of this study support Bandura's (1997) social cognitive theory and previous research (e.g., Chen, 2007) in that mastery experience is a significant source of self-efficacy beliefs. Results also showed a positive relationship between self-efficacy beliefs and English language proficiency when student background information and their learning experience were controlled. Students from the south region reported higher levels of self-efficacy beliefs than their classmates from the north and central regions in Vietnam. However, no significant differences were found between male and female students. Implications of the findings to research and the instruction of English as a foreign language in the Vietnamese context were discussed.